Premium Intraocular Lens Implantation After Laser Vision Correction: An Updated Narrative Review of Biometry, IOL Selection, Visual Outcomes, and Clinical Management - Abdulmohsen Almulhim (Journal of Clinical Medicine, 2026)
Background/Objectives: Premium intraocular lens (IOL) implantation after laser vision correction (LVC) is increasingly common among post-refractive patients seeking cataract and presbyopia management. Therefore, this review aimed to provide a comprehensive updated synthesis of the challenges and outcomes of premium IOL implantation in post-refractive eyes, including visual quality, patient satisfaction, complications, and practical management approaches for patient selection, refractive surprises, and dysphotopsias. Methods and Search Strategies: In this narrative review, relevant articles published in English (January 2016–January 2026) were searched for using appropriate keywords and database indexing terms. The databases used in this review were PubMed/MEDLINE, Embase, Web of Science, and Scopus. Results: A total of 127 studies were included. Across post-LVC subgroups, including LASIK, PRK, SMILE, RK, and hyperopic ablation, premium IOL implantation provided good distance and intermediate-range vision, significant spectacle independence, and high patient satisfaction. Modern techniques, including total keratometry, posterior corneal evaluation, swept-source optical coherence tomography biometry, current post-refractive equations, multi-method comparison, and selective intraoperative aberrometry, have enhanced refractive targeting, with ±0.50 D of target refraction commonly used as a key accuracy benchmark, though not all outliers have been eliminated. However, several key challenges persist, including accurate corneal power estimation, personalization, and accurate lens position, which predispose patients to refractive surprises and a high frequency of dysphotopsias. Furthermore, there is heterogeneity in identifying visual outcomes and vision quality across studies. Conclusions: This review suggests that successful premium IOL implantation in patients after LVC requires individualized planning and structured management protocols. Future studies should standardize quality-of-vision outcomes that compare emerging optics, adjustable technologies, and AI-assisted prediction across post-refractive subgroups.